Nerve Conduction study in healthy individuals, a preliminary age based study - Thakur, D; Paudel, B H; Jha, C B (Kathmandu University Medical Journal, 2012)
Background Nerve conduction study assesses peripheral nerve functions and has clinical implication. Objectives To study the effect of age on nerve conduction study variables in healthy adults. Methods Cross sectional study was done from Jan 2006 to Dec 2006 in department of Physiology, BP Koirala Institute of Health Sciences, Dharan, Nepal. The study was done in 34 (younger, n= 18, 17 to 29 years; older, n= 16, 30 to 57 years) consenting healthy adults of either sex. The compound muscle action potential and sensory nerve action potential were recorded using standard technique. Due to the non-normal distribution of data, the effect of age on nerve conduction study variables was analyzed using Mann Whitney U test. Results Younger vs. older individuals: older had lower Compound Muscle action potential amplitude (mV) in all motor nerves except radial and left ulnar nerves. Compound Muscle action potential duration (ms) was shorter in older (p